Protection of the Rights and Obligations of Indonesian Migrant Workers in the Informal Sector in Saudi Arabia: A Retrospective Study Using Interpretative Phenomenological Analysis - Siti Marwah; Evi Priyanti; Dadan Kurniansyah (Yayasan Adra Karima Hubbi, 2024)
Background. Indonesian migrant workers in the informal sector in Saudi Arabia face serious challenges related to protecting their rights and obligations. Lack of understanding and implementation of safeguards can pose risks to their working and living conditions. Purpose. This research aims to explore the construction of meaning regarding the protection of the rights and obligations of Indonesian migrant workers in Saudi Arabia. The formulation of the problem is: How do Indonesian migrant workers in the informal sector in Saudi Arabia obtain protection of their rights and obligations from the government? What are the main challenges faced by migrant workers regarding the protection of their rights and obligations? Method. This research uses a retrospective study approach with the Interpretative Phenomenology method. Through phenomenological interviews with five people directly involved in Saudi Arabia's informal sector, data was collected to identify the understanding and implementation of protecting the rights of Indonesian migrant workers. This research is based on governance theory which provides a theoretical framework for understanding how the Indonesian government protects the rights of migrant workers abroad and interacts with international institutions. Results. The results of this research indicate the need to increase awareness, understanding and implementation of effective protection for Indonesian migrant workers in Saudi Arabia's informal sector. Cooperation between the Indonesian government and relevant parties in Saudi Arabia needs to be improved to ensure better protection for the rights and obligations of migrant workers. Conclusion. The output of this research is that every Indonesian migrant worker (PMI) is expected to have an electronic Indonesian migrant worker (E-PMI) to protect the rights and obligations of Indonesian migrant workers (PMI) and ensure their identity is officially recorded. By having E-PMI, migrant workers will have better protection and will be safer when working abroad.